2006
DOI: 10.1111/j.1440-1819.2006.01518.x
|View full text |Cite
|
Sign up to set email alerts
|

Topiramate for smoking cessation

Abstract: Due to its AMPA ( α -amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid)/kainate antagonism, topiramate would be particularly interesting in addiction treatment. Flexible-dose topiramate was prescribed to 13 smokers (10 smokers who wanted to stop smoking, and three who received topiramate for other reasons). Six out of 13 smokers were abstinent at 2 months and two more subjects had reduced their cigarette consumption by > 50%. With one exception, temporary reduction of the number of smoked cigarettes preceded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
3
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 14 publications
3
33
3
2
Order By: Relevance
“…The relationship between topiramate and smoking has not, to our knowledge, been previously investigated for this group of smokers. Our findings are consistent with a lack of an effect as reported by Anthenelli et al 5 but contrast the higher rates of abstinence and reduced smoking found by Johnson et al 3 and Khazaal et al 4 . Interestingly, psychotic and mood symptoms in these smokers with schizoaffective disorder were also unaffected (see Changappa et al, 2007 9 .…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The relationship between topiramate and smoking has not, to our knowledge, been previously investigated for this group of smokers. Our findings are consistent with a lack of an effect as reported by Anthenelli et al 5 but contrast the higher rates of abstinence and reduced smoking found by Johnson et al 3 and Khazaal et al 4 . Interestingly, psychotic and mood symptoms in these smokers with schizoaffective disorder were also unaffected (see Changappa et al, 2007 9 .…”
Section: Discussionsupporting
confidence: 73%
“…Few trials have examined topiramate specifically for smoking cessation and findings from these studies have been mixed. Khazaal et al 4 reported that six out of 13 smokers given topiramate (maximum dose 50-225 mg/day for n=11, 500 mg/day for n=1, and 800 mg/day for n=1) were abstinent from smoking after two months with two additional participants reducing their smoking significantly (>50%). In contrast, Anthenelli et al 5 found a trend (p=0.10) towards differences in smoking abstinence with topiramate (200 mg/day) versus placebo in male adult smokers (n=38); however, there was no difference in smoking abstinences rates for female smokers (n=49) by treatment group.…”
mentioning
confidence: 99%
“…Trials investigating topiramate as a specific treatment for smoking cessation led to controversial results. In particular, Khazaal et al (2006) found a significant rate of smoking cessation in a small sample of patients treated with topiramate, while Anthenelli et al (2006) did not find statistical differences between topiramate and placebo, although a trend of reduction in smoked cigarettes was found in male smokers treated with topiramate. A secondary analysis of an 8-week placebo-controlled, randomized clinical trial examining the safety and efficacy of topiramate for patients with schizoaffective disorder, bipolar type, showed a lack of effect on smoking in this subtype of patients (Weinberger et al, 2008).…”
Section: Topiramatementioning
confidence: 91%
“…Entre otras indicaciones se encuentran principalmente el tratamiento del Síndrome de Lenox-Gastaut, prevención de la migraña, trastorno bipolar 1 , tratamiento de la obesidad (al reducir la ingesta incontrolada) y bulimia nerviosa 2 , alcoholismo 3 , trastornos por estrés postraumático 4 , espasmo infantil 5 , cefalea en racimos 6 , tabaquismo 7 , tratamiento del dolor neuropático, especialmente neuralgia del trigémino 8 y síndrome piernas inquietas 9 . Tras su administración oral es rápidamente absorbido, y la mayor parte del fármaco (70%) se excreta en la orina sin modificaciones.…”
Section: Introductionunclassified